Dynamic molecular interactions between polyurethane and ZIF-8 in a polymer-MOF nanocomposite: Microstructural, thermo-mechanical and viscoelastic effects - Mahdi, E; Tan, J (Elsevier, 2016)
Polymer-based nanocomposites incorporating porous hybrid materials is fast becoming a staple in addressing environmental and sustainability challenges. Herein we investigate the intricate dynamics underpinning the molecular interactions between the porous nanoparticles of a zeolitic metal-organic framework (ZIF-8) and ahyperelastic polymer matrix (polyurethane, PU). We fabricated novel PU/ZIF-8 mixed-matrix nanocomposite membranes (~100 µm thickness) with up to 40 wt.% ZIF-8 nanoparticles, and characterised their quasistatic and dynamic thermo-mechanical properties viadynamic mechanical measurements, nanoindentation, thermogravimetric and tensile experiments. ZIF-8 nanoparticles significantly modify the thermo-mechanical properties of polyurethane matrix, improving overall stiffness, fracture energy, and yield strength at the cost of ductility (beyond ~30 wt.%). Thermal stability was enhanced, likewise dynamic responses and phase changes were stabilised with increasing nanoparticle loading. Secondary molecular interactions between ZIF-8 nanoparticles and polyurethane chains are responsible for the salient thermomechanical and dynamic behaviour observed. Our findings may guide developments of resilient rubbery-MOF nanocomposite systems for practical applications.